LIVES IN DEBT AND DISTRESS: A CASE STUDY ON INDEBTEDNESS OF FARMERS IN THE DRY ZONE OF HARYANA STATE, INDIA - Babloo Jakhar; Rohtas Kait; Vijay Kumar (Socio-Economics/Agribusiness Department, 2022)
The study has been conducted to measure the extent and burden of debt on farmers. The study has been conducted to measure the extent and burden of debt on farmers. The study revealed that an average amount of debt per sampled farmer, per owned acre and per operated acre is rupees 491975, 70838 and 62775 respectively. The real burden of debt is very high. Institutional as well as non-institutional sources played main role in loan disbursement to farmers. One third amount of loan is still being taken for non-productive purposes. Conclusions: Farmers are trapped under debt. They are not in situation to rid of from indebtedness. Because, small size of land holding by ownership, non-productive loans and high rate of interests charged by non-institutional sources are the main causes of their indebtedness.